Assessment of the Relation of Mandibular Cortical Index and Gonial Angle Size in an Adult Iranian Population Using Digital Panoramic Radiography - Mirbeigi, Sanam; Tavakoli, Ehsan; Sabaghzadegan, Yasaman; Ezoddiniardakani, Fatemeh; Moshfeghi, Mahkameh (Journal of Dental School, 2019)
Objectives: This study sought to assess the relation of mandibular cortical index (MCI) with age, gender and gonial angle size in an Iranian adult population using digital panoramic radiography. Methods: We evaluated 370 digital panoramic radiographs of patients and divided them into five 10-year age groups. Each radiograph was assigned to low (≤120°) or high (≥125°) angle groups in terms of the gonial angle size. The MCI class was also determined for each individual. The multinomial logistic regression was used to assess statistical differences. Results: The MCI class was significantly different between males and females and MCI class 3 had higher prevalence among older individuals. There was no statistically significant difference in distribution of MCI classes between individuals with high and low gonial angles. Conclusion: Age-related changes in MCI support its potential use for detection of skeletal osteopenia.